An Investigation via Simulation and Measurements to Assess Vehicle Impact on Personal Privacy Device Antenna Radiation Patterns. Issue 2 (September 2015) - Aloi, Daniel N.; Alkhateeb, Abualkair M.
Abstract This article presents a study of the radiation pattern of a personal privacy device (PPD) antenna on a fabricated vehicle and three commercial vehicles. Initially, electromagnetic modeling of the PPD antenna on the fabricated vehicle in three distinct antenna locations and two orientations per location was performed. Measurements were then conducted to gauge the accuracy of the simulations. Next, the same PPD antenna was placed in three locations and two orientations per location on three commercial vehicles to create 18 unique configurations. The maximum right hand circularly polarized gain vs. theta angle was analyzed. The results show that electromagnetic modeling of antennas mounted inside a vehicle differ significantly from measurements of the same scenario but acceptable agreement was achieved for exterior‐mounted antennas on a vehicle. It also provides a vehicle efficiency value corresponding to the vehicle body frame's impact on a component‐level PPD antenna radiation pattern over theta angles. Copyright © 2015 Institute of Navigation.